Aliceheimer's : Alzheimer's through the looking glass - Walrath, Dana (Graphic medicine., 2016)
"A graphic memoir of the author's experiences of her mother's battle with dementia. Illustrates the two-way nature of storytelling as a process that heals both the giver and the receiver of story"--Provided by publisher.